STUDY OF THE RELATIVE EFFECTIVENESS OF EXTENSION METHODS IN EDUCATING FISHER WOMEN - THIAGARAJAN, R; KANDORAN, M K; THOMAS, MARY (Fishery Technology, 2017)
Three experimental groups from three different fishing villages were selected and administered with three extension treatments on two messages, namely, production of fish wafers and fish pickles. There was a significant knowledge gain in the subjects taught through different extension methods. It was observed that lecture aided with slides induced maximum knowledge followed by lecture aided with charts and lecturealone. Among all, the young and highly educated women gainedmaximumknowledge.